2003
DOI: 10.1590/s0102-86502003000600007
|View full text |Cite
|
Sign up to set email alerts
|

Ascite neoplásica: efeito da solução aquosa de fenol, ácido acético e glicerina sobre o tumor ascítico de Ehrlich

Abstract: OBJETIVO: Verificar o efeito da solução composta por fenol, ácido acético e glicerina sobre o tumor ascítico de Ehrlich. MÉTODOS: Utilizou-se 283 camundongos divididos em 2 protocolos (animais portadores e não portadores de tumor) procedendo-se a injeção de 0,25 ml, 0,10 ml e 0,05 ml da solução teste e 0,25 ml de solução salina, o sacrifício foi realizado após 3 e 6 dias do tratamento, analisando, a seguir, a contagem diferencial de células presentes no líquido ascítico. RESULTADOS: Observou-se que nos animais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
3

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 14 publications
0
10
0
3
Order By: Relevance
“…In a previous study, we used a solution composed of acetic acid, glycerin and phenol in the treatment of Ehrlich ascites tumor cells. We observed that the in vitro solution destroyed tumor cells and increased the number of inflammatory cells 4 . Therefore, it seemed appropriate to test one or more of these components separately in the livers of animals with tumors.…”
Section: Overviewmentioning
confidence: 81%
See 1 more Smart Citation
“…In a previous study, we used a solution composed of acetic acid, glycerin and phenol in the treatment of Ehrlich ascites tumor cells. We observed that the in vitro solution destroyed tumor cells and increased the number of inflammatory cells 4 . Therefore, it seemed appropriate to test one or more of these components separately in the livers of animals with tumors.…”
Section: Overviewmentioning
confidence: 81%
“…In a study performed in 1996 4 , we analyzed the effects of a solution consisting of acetic acid, glycerin, phenol and distilled water on Ehrlich ascites tumor cells in vitro and in vivo and observed that the solution caused tumor cell death in vitro. Intraperitoneal injection of the solution in vivo reduced the number of tumor cells and increased the number of inflammatory cells in suspension in the acetic acid solution 4 . In light of this observed effect, we decided to analyze the possible effects of one or more of the solution components in isolation.…”
Section: Introductionmentioning
confidence: 99%
“…After 3 days of tumour development, the compounds [{Pd(dmba)} 2 (μ-NCS) 2 ] (1), [Pd(dmba) (NCS)(dppp)] (2) and cis-DDP were inoculated, according to literature methods. 18 Groups were named according to the compounds inoculated:…”
Section: In Vivo Assaysmentioning
confidence: 99%
“…After 3 days of tumour development, the compounds [{Pd(dmba)} 2 (μ-NCS) 2 ] (1), [Pd(dmba) (NCS)(dppp)] (2) and cis-DDP were inoculated, according to literature methods. 18 Groups were named according to the compounds inoculated:Group 1 or G1: cis-DDP (1 mL, i.p., 10 mg kg -1 ); Group 2 or G2: [Pd(dmba)(NCS)(dppp)] (1 mL, i.p., 1 mmol L -1 ); Group 3 or G3: [{Pd(dmba)} 2 (μ-NCS) 2 ] (1 mL, i.p., 1mmol L -1 ); Group 4 or G4: Vehicle control (1mL, i.p., DMSO 0.3%); Group 5 or G5: Tumour control (1mL, i.p., PBS). …”
mentioning
confidence: 99%
See 1 more Smart Citation